Is Teal Swan a Cult Leader, Supplier of Bad Advice, or Both? | "The Deep End" Analysis - Dr. Todd Grande (2022)
This video answers the question: Can I analyze the Hulu documentary “The Deep End,” which is about the self- proclaimed spiritual guru Teal Swan? Support Dr. Grande on Patreon: https://www.patreon.com/drgrande Subscribe to the Bella Grande Media Podcast: / @bellagrandemedia Dr. Grande’s book Harm Reduction: https://www.amazon.com/Harm-Reduction... Dr. Grande's book Psychology of Notorious Serial Killers: https://www.amazon.com/Psychology-Not... Check out Dr. Grande’s merchandise at: https://teespring.com/stores/dr-grand... References: https://decider.com/2022/05/20/the-de... https://www.autostraddle.com/the-deep... • Documentary Episo...